The Role of Organizations in Developing Students' Soft Skills at UKM SINTALARAS UNM - Uhud Darmawan Natsir; Muh. Awaluddin; Agung Widhi Kurniawan; Burhanuddin Burhanuddin (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia, 2025)
The Student Activity Unit for Environmental Lovers at Makassar State University is one of the organizations within the scope of Makassar State University which is very important to know about its role in developing the soft skills of its members. Data obtained through interviews with 9 informants were divided into 3 types, namely key informants, namely alumni, expert informants, namely demissioners, then additional informants, namely administrators. The aim of this research is to determine the role of student organizations in developing student soft skills in the Student Activity Unit for Environmental Lovers at Makassar State University. The results of the research show that the Makassar State University Student Activities Unit for Environmental Lovers in Harmony has a role in developing the soft skills of students who are members of this organization. Activities in the Student Activity Unit organization for Environmental Lovers at Makassar State University indirectly develop the soft skills of students who are members of this organization.